Use of mindfulness in coping with incivility - Green, Cheryl (Nurse Educator, 2017)
Keywords: dept.nur; peer-reviewed

New nursing faculty and incivility: applying mindfulness-based strategies - Green, Cheryl (Holistic Nursing Practice, 2018)
Workplace incivility remains a problem within the nursing profession. As nurse leaders, we must recognize and not ignore the complexity of cultures that have adapted incivility into the work environment. Nursing education is a discipline that requires collaborative team work, independent drive, and commitment. New nursing faculty experiencing incivility can use mindfulness-based meditation approaches to cope with uncivil behaviors experienced within the workplace. Nurse educators applying the concepts of mindfulness can learn how to provide themselves self-care by reducing stress, as enhanced daily awareness of peace and calm are incorporated into their lifestyle. Mindfulness provides a realization that control can only be given to other persons when an individual allows or accepts another's negative behaviors. Awareness of the value and importance of oneself can assist the nurse educator experiencing incivility to maintain his or her emotional, physical, and spiritual health despite the volatility of the work environment.
Keywords: Attitude of Health Personnel; Bullying; Faculty, Nursing; Humans; Incivility; Interprofessional Relations; Mindfulness; Stress, Psychological; Universities; Workplace; academia; adult; awareness; bullying; complication; dept.nur; etiology; female; health personnel attitude; human; human experiment; incivility; leadership; lifestyle; male; meditation; mental stress; mindfulness; nursing education; nursing faculty; occupation; organization and management; peer-reviewed; psychology; public relations; self care; standards; stress; teamwork; trends; university; work environment; workplace

Incivility among nursing professionals in clinical and academic environments: emerging research and opportunities - Green, Cheryl (IGI Global, 2018)
Traditionally, nursing is acknowledged as a caring profession and is associated with advocating for others. However, incivility is increasingly occurring amongst nurses, both in the clinical and academic environments, and is causing affected nurses both psychological and physical harm. Incivility Among Nursing Professionals in Clinical and Academic Environments: Emerging Research and Opportunities provides emerging views and consequences surrounding workplace bullying in the healthcare profession including recognizing the signs and symptoms of incivility in the workplace, identifying ways in which affected nurses can seek help, and examining healthy methods of coping with the incivility. Featuring coverage on a broad range of topics such as human resources, therapy, and clinical nursing, this book is ideally designed for nurses, managers, healthcare workers and consumers, hospital and clinical staff, researchers, students, and policymakers.
Keywords: dept.nur

Using case study methodology to explore the role of discrimination in workplace incivility - Green, Cheryl (Journal of National Black Nurses' Association: JNBNA, 2018)
Exclusionary behaviors can be detrimental to the health and well-being of faculty in the workplace. When colleagues are judged by their peers because of the color of their skin, the language they speak, their gender, or who they choose to love (lesbian, gay, bisexual, transgender, asexual, or questioning), affected faculty are left emotionally and physically vulnerable. Institutions of higher learning must set standards of zero tolerance for faculty-to-faculty incivility. With standards taken from each faculty discipline, codes of conduct can be implemented not only at a departmental level, but also throughout the educational system.
Keywords: Discrimination; Exclusionary; Faculty; Humans; Incivility; Interprofessional Relations; Prejudice; dept.nur; peer-reviewed

Using instrumentation in psychiatric nursing to assess documentation of the nursing process for emergent non-psychiatric patient events. - Green, Cheryl (Archives of Psychiatric Nursing, 2018)
Ongoing education of experienced psychiatric nurses is imperative given the historically complex health presentations of psychiatric patients. Psychiatric patients tend to have medical co-morbidities and often do not have the financial resources for preventative health care. The hospitalization for acute psychiatric stabilization, is an opportunity for psychiatric nurses to teach and advocate for patients' physiological and psychological health. Documentation of patients' changes in condition and overall clinical presentation, is necessary to ensure patients' health care needs are met. Copyright © 2018 Elsevier Inc. All rights reserved.
Keywords: *Documentation/st [Standards]; *Inservice Training/mt [Methods]; *Nursing Process; *Psychiatric Nursing; Documentation; Educational Measurement; Educational Measurement/sn [Statistics & Numerical Data]; Hospitalization; Humans; Inservice Training; Nurses; Nursing Process; Nursing process; Patients; Psychiatric Nursing; Psychiatry; Surveys and Questionnaires; adult; article; comorbidity; dept.nur; documentation; education; health care need; hospitalization; human; in service training; mental patient; nurse; nursing process; peer-reviewed; procedures; psychiatric nursing; psychological well-being; questionnaire; standards; statistics and numerical data

Contemporary issues: The pre-licensure nursing student and medication errors. - Green, Cheryl (Nurse Education Today, 2018)
In Modern health care, the creation of cultures of safety for patients is of the upmost importance. Impacting the institutional stabilization of health care facilities safety initiatives, is the preparation of pre-licensure nursing students to safely administer medications to patients. Therefore, preparation of the pre-licensure nursing student must be evidence-based practice focused and incorporate innovative ways to reduce the potential for medication errors. Copyright © 2018. Published by Elsevier Ltd.
Keywords: *Clinical Competence; *Medication Errors/nu [Nursing]; *Students, Nursing; Clinical Competence; Education, Nursing, Baccalaureate; Humans; Licensure, Nursing; Medication Errors; Medication Errors/pc [Prevention & Control]; Medication errors; Pre-licensure nursing students; Prevention; Students, Nursing; adult; clinical competence; dept.nur; drug safety; editorial; evidence based practice center; health care facility; human; licensing; medication error; nursing; nursing education; nursing student; peer-reviewed; prevention and control

Cultural considerations in the care of psychiatric patients: a case study on fright - Green, Cheryl (Journal of National Black Nurses Association, 2019)
Keywords: Cultural Competence; Cultural Sensitivity; Fear; Female; Health Care Delivery; Medicine, Herbal; Multidisciplinary Care Team; Patient Centered Care; Psychiatric Patients; Young Adult; dept.nur; peer-reviewed; ⛔ No DOI found

Exploring clinical environmental awareness and its impact on patient safety - Green, Cheryl Ann (2017)
Keywords: dept.nur; ⛔ No DOI found

Interprofessional health promotion - Green, Cheryl Ann (2017)
Keywords: dept.nur; ⛔ No DOI found

The elderly and the opioid epidemic: A case study - Green, Cheryl A. (Addictive Disorders & Their Treatment, 2017)
Opioid addiction is a problem within the United States that is impacting all age groups. The elderly are a population that is seldom discussed as being affected by opioids. Physiologically, the older adult is more susceptible for complications associated with an alteration in pharmacokinetics and late diagnosis of diseases such as viral hepatitis C. Health promotion for this population is imperative in the prevention and treatment of opioid addiction problems.
Keywords: Article; Hepatitis C virus; United States; aged; boceprevir; buprenorphine plus naloxone; case report; clinical article; creatinine; creatinine blood level; dept.nur; diamorphine; follow up; health care personnel; health promotion; hepatitis C; human; male; medicare; methadone; methadone treatment; older adults; opiate addiction; opioids; oxycodone; priority journal; protein blood level; self report; telaprevir; urea nitrogen blood level; weight reduction

Understanding the complexities of the effects of incivility on the victim and using mindfulness to heal - Green, Cheryl Ann (International Journal of Health, Wellness & Society, 2018)
The complexity of the human body is such that any disturbances to its homeostatic state, unreversed, can lead to the development of illness or disease. When one considers the terminology of incivility as a concept, one does not automatically equate this concept with disease or illness. However, incivility left to persist in work environments can prove mentally and physically damaging to the victim. Mindfulness can be used as a means to help nurses experiencing workplace incivility, to begin the process of emotional and physical healing.
Keywords: EMOTIONS (Psychology); HOMEOSTASIS; Illness; Incivility; MINDFULNESS; Mindfulness; NURSES; Nurses; WORK environment; Work Environment; dept.nur; peer-reviewed

Complimentary Care: When Our Patients Request to Pray. - Green, Cheryl Ann (Journal of Religion and Health, 2018)
Prayer is viewed in modern medicine as a complimentary alternative treatment. However, to many patients, it is a source of hope and comfort. Patients, when facing illness, advanced disease, disability or death, can benefit from prayer. For healthcare providers, comfort with praying with patients can be deemed as unprofessional conduct or blurred therapeutic boundaries, particularly, when prayer is offered to patients' unsolicited by the patient or their family member(s). Therefore, it is imperative that healthcare providers await the request of prayer by the patient before prayer is initiated.
Keywords: *Attitude of Health Personnel; *Delivery of Health Care; *Faith Healing; *Pastoral Care/mt [Methods]; *Religion; *Spirituality; Attitude of Health Personnel; Delivery of Health Care; Faith Healing; Family; Healthcare providers; Humans; Nurse's Role; Nurses; Pastoral Care; Patients; Prayer; Religion; Religion and Medicine; Spirituality; dept.nur; family; health care delivery; health personnel attitude; human; nurse attitude; pastoral care; peer-reviewed; procedures; religion; spiritual healing

Identification of patients' spiritual needs using a spiritual health assessment tool - Green, Cheryl Ann (Creating Healthy Work Environments, 2019)
Keywords: dept.nur; ⛔ No DOI found

Workplace incivility: Nurse leaders as change agents - Green, Cheryl Ann (Nursing Management, 2019)
An abstract is unavailable.
Keywords: Humans; Interprofessional Relations; Leadership; Nursing Staff; Organizational Innovation; Workplace; dept.nur; human; leadership; nursing staff; organization; peer-reviewed; public relations; workplace

Calm in Chaos: Prose on Tensions of Hate and Distrust in Society - Green, Cheryl; Green, Joshua William (Westbow Press, 2019)
Keywords: Hate; Poetry; Poetry; Racism; dept.nur; faculty_collection